Local communities and tourists' perception towards to PLTD Apung sites as tsunami disaster tourism in Banda Aceh City. (March 2018) - Fahmi, U; Ginting, N; Sitorus, R
Abstract: Earthquake and tsunami disasters that hit Banda Aceh city a few years ago, it can be classified as the most terrible natural disasters in the history of the world. Natural disasters were considered as a scary incident, also leave a lot of losses, both regarding moral and material for victims. The establishment of the tourism as media of preservation disaster could be something interesting and demand by the community, especially in the preservation of disaster that usually contains a different perspective. One of the silent witness the awesomeness of tsunami wave that preserves as disaster tourism is tsunami education park, PLTD Apung sites that located in the sub-district of Punge Blang Cut, District of Meuraxa, Banda Aceh city. The community and tourists that interact to tourism object can give the impression, assessment, opinion, felt and interpret something toward to information that displayed. The existence of development experience, ability to think, terms of reference are not the same for each in the community as well as tourists, make it possible to generate a different perception of development. The purpose of this research is to know Community and Tourists Perceptions towards to PLTD Apung sites as Tsunami Disaster Tourism in the sub-district of Punge Blang Cut, Banda Aceh city. This research will conduct by using the descriptive-qualitative method. The research goal is to be recommendations include development activity areas and participation are supposed to do by local community and tourists. In the recommendation is defined procedures development of PLTD Apung sites that considered to community and Tourists Perception. It is expected to optimize the development of PLTD Apung sites that can be an identity of tsunami disaster tourism in Banda Aceh city.